2011
DOI: 10.1590/s1678-91992011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Envenomations caused by different species of Bothrops snakes result in severe local tissue damage, hemorrhage, pain, myonecrosis, and inflammation with a significant leukocyte accumulation at the bite site. However, the activation state of leukocytes is still unclear. According to clinical cases and experimental work, the local effects observed in envenenomation by Bothrops alternatus are mainly the appearance of edema, hemorrhage, and necrosis. In this study we investigated the ability of Bothrops alternatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Studies have showed generation of reactive oxygen species (ROS) by macrophages and peritoneal leukocytes stimulated with Bothrops sp. snake venoms (97, 102). Further, increased production of hydrogen peroxide and nitric oxide by macrophages followed by generation of peroxynitrites induced by Bothrops snake venoms (103) and the ability of Vipera russelli , a snake of medical importance in Asia, to activate production of ROS in neutrophils were also described.…”
Section: Inflammation Induced By Viper Snake Venommentioning
confidence: 99%
“…Studies have showed generation of reactive oxygen species (ROS) by macrophages and peritoneal leukocytes stimulated with Bothrops sp. snake venoms (97, 102). Further, increased production of hydrogen peroxide and nitric oxide by macrophages followed by generation of peroxynitrites induced by Bothrops snake venoms (103) and the ability of Vipera russelli , a snake of medical importance in Asia, to activate production of ROS in neutrophils were also described.…”
Section: Inflammation Induced By Viper Snake Venommentioning
confidence: 99%
“…Again, BAV-treatment showed a limited impact on MF viability, as evaluated by Trypan blue exclusion, and did not interfere with MF's adhesion or detachment capacity up to 100 µg/mL BAV (49). Pretreatment with the protein kinase C inhibitor, staurosporine (14 nM/mL), suppressed O − 2 production and phagocytosis, suggesting the involvement of a PKC-dependent signalling pathway (49). However, unlike CDTV, Setubal et al observed increased MF complement receptor (CR3)-mediated phagocytosis following incubation with BAV (49).…”
Section: Mononuclear Phagocytic Systemmentioning
confidence: 85%
“…2 ) from isolated thioglycollate-elicited MFs (49). Again, BAV-treatment showed a limited impact on MF viability, as evaluated by Trypan blue exclusion, and did not interfere with MF's adhesion or detachment capacity up to 100 µg/mL BAV (49).…”
Section: Mononuclear Phagocytic Systemmentioning
confidence: 86%
See 2 more Smart Citations